Education and Training Practices in Four Selected Malaysian Manufacturing Companies - Karuppiah, Karmegam (2004)
One of the company's major problems in education and training is how to identify the results of investments and human resources and how to compare these results with those of others. The lack of good comparative information on education and training expenditures has fixstrated training decision makers, to make decisions about training and comparing the results with some standards. The objective of this case study is to identify investments and human resource practices in the education and training in selected companies. Information obtained on education and training from the respondent companies will be compared with the American Society of Training and Development (ASTD) database. These results will serve as a benchmark in education and training in these selected companies. This study was done using adapted questionnaire which are designed by the American Society for Training and Development (ASTD). The questionnaire was sent to 4 selected manufacturing companies from Small and Medium Industries Development Corporation (SMDEC), Enterprise 50 award winners. The data collected from the 4 companies was compared with the ASTD database The results showed that the selected companies are giving less importance to employees' education and training compared to ASTD database. Companies A, B, C and D, overall investments such as total training expenditures per employee (RM), total hours of training eligible employees, trainers' wages and salaries per employee (RM) and training payments to outside companies per employee (RM) were less than the ASTD expenditures. Companies A, B, C and D are using more on classroom delivery method as a tool of training delivery to their employees. The result also showed that Companies A, B, C and D provided more on management and skill type of training to their middle managers, first-line managers and production employees. Based on this study, some recommendations are made for the Companies A, B, C and D. These companies should increase its employee's education and training expenditures as this are important to produce a good quality workforce. It also needs to use more new methods of training delivery. It should take advantage of learning technologies and try to use electronic or computer-based training methods such as CD-ROMs, Electronic Performance Support System (EPSS) and web-based learning. These companies also needs to improve its education and training contents such as the type of training provided, type of employee received training and the amount time of IT training. Type of training provided should included management, soft skills and technical skill training topic. The training should be provided to all type of employee in the Companies A, B, C and D. Overall this study provided the selected companies with helpful data to monitor and improve the effectiveness of their employees' education and training system